PENERAPAN GLOBAL EXTREME PROGRAMMING PADA SISTEM INFORMASI WORKSHOP, SEMINAR DAN PELATIHAN DI LEMBAGA EDUKASI - Baginda Oloan Lubis (Jurnal Informatika, 2016)
Abstract Institutions of education as one of the service agencies workshops, seminars and training with information systems that are still manual at the time of printing id cards, the manufacture of attendance, printing certificates and report generation often had difficulty in searching data and other impacts arising from manual systems. Therefore the design of information systems or desktop based application creation is a solution to provide convenience to the user in the process of data processing, data retrieval to preparing reports. Model systems development workshops, seminars and training used in the design of information systems workshops, seminars and training using a model of Agile Software Development, which was discovered and developed by Robert Cecil Martin with process models Global Extreme Programming, namely the development of XP (Extreme Programming) Life Cycle. While the tools used by the UML (Unifed Modeling Language) and ERD (Entity Relationship Diagram). Hopefully, by the design of this system will allow a user who uses the id card printing, manufacture of attendance, certificate printing and reporting each end of the activity.